Local Community Resistance to Geothermal Projects in Indonesia - Davina Putri Hanum; Yeby Ma'asan Mayrudin (Journal of Governance Innovation, 2026)
This study seeks to provide a broader perspective on geothermal development in Indonesia, arguing that community rejection of projects is not merely an emotional reaction, but also a call to pay attention to their neglected rights and needs. This study aims to comprehensively understand how implementation practices and local social conditions shape the dynamics of acceptance or rejection of geothermal projects in Indonesia. The researchers used the Systematic Literature Review (SLR) method to examine various scientific sources in a structured and comprehensive manner. Referring to Kitchenham's (2015) guidelines, the SLR was conducted in three main stages: planning, implementation, and reporting. This method was using SCOPUS and Crossreff as the main data sources. results of the study show that resistance to geothermal energy projects in Indonesia is rooted in the view of natural resources as strategic commodities, resulting in centralized and top-down governance. This places the state and corporations as the main actors and marginalizes the participation of local communities. Case studies such as Salingka Gunung Talang, Padarincang, and Waplasit village reveal the socio-ecological irony that projects claimed to be sustainable have led to new poverty, relocation, health vulnerabilities, social disintegration, and the neglect of indigenous peoples' cultural values.